Turk Arch Pediatrics 2022
DOI: 10.5152/turkarchpediatr.2022.22012
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Involvement in Pediatric COVID-19 Cases: A Single-Center Experience

Abstract: Objective: The kidney is the second most commonly affected organ by severe acute respiratory syndrome coronavirus-2, characterized by hematuria, proteinuria, and acute kidney injury. There are few studies describing renal involvement in pediatric cases. Materials and Methods: This retrospective study evaluated the prevalence of hematuria, proteinuria, and acute kidney injury in severe acute respiratory syndrome coronavirus-2-positive pediatric cases (1-18 years old) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The incidence of these two parameters was not as high as in the previously mentioned studies; however, it can predict adverse renal outcomes in long-term follow-up since Omicron infections may cause new kidney involvement [45]. for GLU [7,8,11]; for LEU (a) severe and critical COVID-19 [7,8,42], (b) COVID-19 AKI [25]; for KET [16]; for SG [4,5,10,16]; for BLOOD (a) severe and critical COVID-19 [7,8,10,11,29], (b) COVID-19 AKI [16,22,44], (c) COVID-19 mortality [14,16].…”
Section: Urine Biochemical Parameters For the Diagnosis And Predictio...mentioning
confidence: 78%
See 3 more Smart Citations
“…The incidence of these two parameters was not as high as in the previously mentioned studies; however, it can predict adverse renal outcomes in long-term follow-up since Omicron infections may cause new kidney involvement [45]. for GLU [7,8,11]; for LEU (a) severe and critical COVID-19 [7,8,42], (b) COVID-19 AKI [25]; for KET [16]; for SG [4,5,10,16]; for BLOOD (a) severe and critical COVID-19 [7,8,10,11,29], (b) COVID-19 AKI [16,22,44], (c) COVID-19 mortality [14,16].…”
Section: Urine Biochemical Parameters For the Diagnosis And Predictio...mentioning
confidence: 78%
“…The studies presented by Yildirim, C. et al [ 9 ] and Bassoli, C et al [ 11 ] evaluated PRO as an early predictor of COVID-19-related renal damage [ 9 , 11 ]. The study of Baulos et al [ 42 ] and Sharma et al [ 31 ] confirmed that abnormal urinalysis results, such as PRO, haematuria, and LEU were higher in severe COVID-19 infection and also in patients who died of the disease [ 29 , 31 , 42 ]. Observations from patients affected with the Omicron COVID-19 infection in the post-acute treatment phase were reported.…”
Section: Methods: Identification and Characteristics Of Included Studiesmentioning
confidence: 94%
See 2 more Smart Citations